Preparation and Evaluation of Liquid and Solid Self-Microemulsifying Drug Delivery System of Mebendazole - Ahmed A. Hussein (College of Pharmacy University of Baghdad, 2017)
The aim of present study was to develop solid and liquid  self-microemulsifying drug  delivery system of poorly water soluble drug mebendazole using Aerosil 200 as solid carrier.  Microemulsions are clear, stable, isotropic liquid mixtures of oil, water and surfactant, frequently in combination with a co-surfactant having droplet size range usually in the range of 20-250 nm. Oleic acid, tween 80 and polypropylene glycol were selected as oil, surfactant and co-surfactant respectively and for preparation of stable SMEDDS, micro emulsion region was identified by constructing pseudo ternary phase diagram containing different proportion of surfactant: co-surfactant (1:1, 2:1 and 3:1), oil and water. In brief S/ CoS mix means surfactant to co-surfactant and oil were mixed at ratio of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1 manner. To the resultant mixtures, water was added drop wise till the first sign of turbidity in order to identify the end point and after equilibrium; if the system became clear then the water addition was continued. Prepared optimised formula of microemulsion was evaluated for SEM, particle size analysis, polydispersity index, phase separation, viscosity determination, zeta potential, in- vitro dissolution study and in- vivo studies. The optimized microemulsion was converted into solid form by Spray Drying technique by using Aerosil 200 as solid carrier. Prepared SMEDDS was characterized for same parameters as that of microemulsion. Solid SMEDDS of mebendazole prepared using Aerosil 200 by spray drying technique showed good drug content uniformity. After reconstitution it formed microemulsion with micrometric range. In-vitro drug release and in-vivo plasma drug concentration of microemulsion and SMEDDS was much higher than that of marketed praparation. Hence lipid based drug delivery system may efficiently formulate microemulsion and it can be solidified easily by spray drying technique which enhances dissolution rate and thus concomitantly bioavailability. In conclusion ,self micro emulsifying drug delivery system has become promising tool to overcome shortcomings associated with conventional delivery. Kew words: Self-microemulsifying drug  delivery system, Microemulsion, Mebendazole.